2020
DOI: 10.1007/s10916-019-1499-7
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Online Continuing Education in Radiology for General Practitioners

Abstract: The aim of this study was to determine whether e-learning as a new teaching methodology was acceptable for general practitioners in continuous education courses of radiology. Generally, these courses are face-to-face with the corresponding time and place limitations. To overcome these limitations, we transformed one of these courses to an online one evaluating its acceptance. The course was about thorax radiology and it was delivered to 249 participants. The experiment was carried out in two phases: Phase 1, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…At the time, our imaging database had many cases to illustrate all the aforementioned considerations. For this reason, we decided to create an online course using our previous experience in e-learning methodologies [ 48 ] and e-learning platform development [ 37 ]. The course was created to help professionals identify findings suggesting pulmonary involvement by COVID-19 through CXR images, as well as other findings that could point to other pathologies.…”
Section: Methodsmentioning
confidence: 99%
“…At the time, our imaging database had many cases to illustrate all the aforementioned considerations. For this reason, we decided to create an online course using our previous experience in e-learning methodologies [ 48 ] and e-learning platform development [ 37 ]. The course was created to help professionals identify findings suggesting pulmonary involvement by COVID-19 through CXR images, as well as other findings that could point to other pathologies.…”
Section: Methodsmentioning
confidence: 99%
“…While this transition had already begun, the pandemic expedited this process. Recent studies have shown that learning radiology through virtual platforms is viable, comparable, and positively perceived compared to in‐person learning, resulting in the same skills and learner performance compared to in‐person lessons 18–22 …”
Section: Introductionmentioning
confidence: 99%
“…In classrooms, this has been supported through the use of case‐based learning, but there is also strong evidence of providing immediate feedback following application problems. With instructors as facilitators for discussion, it was shown that this immediate feedback from instructors supported higher processing of the information, and thus more learning 22,32 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also supported the effectiveness of online CME in terms of physicians’ satisfaction, knowledge gain, and behavioral changes [ 6 , 7 ]. Interestingly, a recent study concluded that physicians were open to the idea of online CME programs as a substitute for face-to-face courses as they encouraged more participation in CME, promoted more engagement, and reduced the need and time to travel [ 8 ].…”
Section: Introductionmentioning
confidence: 99%